Pengaruh Pelatihan dan Pemberian Insentif terhadap Kinerja Kader Kesehatan melalui Motivasi Kerja sebagai Variabel Intervening - Muhammad Anton (Jurnal Syntax Admiration, 2024)
This research aims to determine the effect of training and providing incentives on the performance of health cadres through work motivation as an intervening variable in the Rembang I Community Health Center Work Area, Rembang Regency. The type of research is quantitative with a descriptive survey form. Research design with a causal pattern. The population in this study was 510 Health Cadres in the Rembang I Community Health Center Working Area using a purposive sampling technique. The sample size was 200 respondents. Data collection methods and using questionnaires. The data analysis used is descriptive analysis and quantitative analysis using Structural Equation Modeling (SEM). The results and implications of this research theoretically are that training and incentives have a significant positive effect on motivation. Training, incentives and motivation have a significant positive effect on cadre performance. Motivation can significantly act as an intervening link between training and the performance of health cadres. Motivation has not been able to significantly act as an intervening link between providing incentives and the performance of health cadres.